Estimating outstanding claims reserves using copula. - Kee, Meng Yew. (2010)
Outstanding claims reserves in general insurance are a type of technical reserve or accounting provision in the financial statements of an insurer. One of the most popular statistical methods in claims reserving is the Chain Ladder Method. This method, however, has been shown to suffer from several drawbacks. For example, it discards a significant amount of information, which may be important to accurately estimate the outstanding claims reserves. In this research, an alternative method, by using Archimedean copulas, is proposed to estimate the reserves. The copula method is then evaluated and compared with the chain ladder method based on a real data set. The findings show that the estimated outstanding claims reserves using the copula method is closer to the actual outstanding claims paid out compared to the Chain Ladder Method. This suggests that the copula method is a more accurate and viable alternative to the conventional method in estimating the outstanding claims reserves.